Town council scrivener's offices : occupation and succession on the job accordin with minute books (Madrid, 1557-1610) : a methodological proposal (Estudios de Historia de España, 2021)
The occupation and succession of Early Modern Madrid’s town council scrivener’s offices are studied here, from a historical point of view (years 1557 to 1610). Certain information from Minute Books are systematically analysed (certain mentions and receptions in the job), as far as certain information gaps (absence of validation signs). The result reveals not only who was the owner or the substitute of the job, but, which is more, who worked officially or informally. Scriveners’ family ties are also regarded to show off endogamy links. Diagrams are proposed to summarize the succession on the scrivener’s offices, together with the parental and labour relationships, as a kind of genealogies on the job.
Keywords: Notaries; City council; Municipality; Madrid (Spain); Early Modern Age; Methodology